Highly Stable Transparent Conductive Silver Grid/PEDOT:PSS Electrodes for Integrated Bifunctional Flexible Electrochromic Supercapacitors. Issue 4 (7th December 2015) - Cai, Guofa; Darmawan, Peter; Cui, Mengqi; Wang, Jiangxin; Chen, Jingwei; Magdassi, Shlomo; Lee, Pooi See
Abstract : Silver grids are attractive for replacing indium tin oxide as flexible transparent conductors. This work aims to improve the electrochemical stability of silver‐based transparent conductors. A silver grid/PEDOT:PSS hybrid film with high conductivity and excellent stability is successfully fabricated. Its functionality for flexible electrochromic applications is demonstrated by coating one layer of WO3 nanoparticles on the silver grid/PEDOT:PSS hybrid film. This hybrid structure presents a large optical modulation of 81.9% at 633 nm, fast switching, and high coloration efficiency (124.5 cm 2 C −1 ). More importantly, an excellent electrochemical cycling stability (sustaining 79.1% of their initial transmittance modulation after 1000 cycles) and remarkable mechanical flexibility (optical modulation decay of only 7.5% after 1200 compressive bending cycles) is achieved. A novel smart supercapacitor is presented that functions as a regular energy‐storage device and simultaneously monitors the level of stored energy by a rapid and reversible color variation even at high current charge/discharge conditions. The film sustains an optical modulation of 87.7% and a specific capacitance of 67.2% at 10 A g −1 compared to their initial value at a current density of 1 A g −1 . The high‐performance silver grid/PEDOT:PSS hybrid transparent films exhibit promising features for various emerging flexible electronics and optoelectronic devices. Abstract : By coating a layer of PEDOT:PSS on a silver grid film, a highly stable transparent and conductive hybrid film has been successfully fabricated by a facile and low‐cost method. It presents an excellent electrochemical cycling stability, a remarkable mechanical flexibility, and an outstanding electrochromic and energy‐storage performance when used as flexible electrochromic supercapacitor electrodes.